Aerosol Processing of Crumpled Graphene Oxide-based Nanocomposites for Drug Delivery - Wang, Wei-Ning; He, Xiang (Current Pharmaceutical Design, 2016)
Background: The flexibility of graphene oxide (GO) nanosheets and their unique properties enable them to be excellent two dimensional (2D) building blocks for designing functional materials. Aerosol routes are proved to be a rational approach to fold the 2D flat GO nanosheets into 3D crumpled spheres to mitigate the restacking issue for large-scale applications, such as for drug delivery. Results: The fundamentals of graphene, GO, and the crumpling process of GO nanosheets are summarized. Various crumpled graphene oxide (CGO)-based nanocomposites have been synthesized by aerosol routes. This mini review focuses on the state-of-the-art in the design and fabrication of these nanocomposites for a specific application in drug delivery. Various techniques are demonstrated and discussed to control the release rates, tailor the morphology, and adjust the components inside the nanocomposites. Potential risks and possible trends are also pointed out. Conclusion: Aerosol processing of CGO-based nanocomposites provides a promising approach to design functional nanomaterials for drug delivery and other related applications.
Keywords: capillary force